2017
DOI: 10.1097/aln.0000000000001612
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Characteristics of Death in Intensive Care Units

Abstract: Background Different modes of death are described in selected populations, but few data report the characteristics of death in a general intensive care unit population. This study analyzed the causes and characteristics of death of critically ill patients and compared anticipated death patients to unexpected death counterparts. Methods An observational multicenter cohort study was performed in 96 intensive care units. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 16 publications
5
42
0
2
Order By: Relevance
“…In our study, 45% of patients for whom life support was withheld in the ICU were discharged. In accordance with the findings of previous studies, we found that half of the deaths in the ICU occurred after the decisions to withhold or withdraw life support . Among those patients for whom life support was withheld, 58.8% were still alive 6 months post‐discharge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, 45% of patients for whom life support was withheld in the ICU were discharged. In accordance with the findings of previous studies, we found that half of the deaths in the ICU occurred after the decisions to withhold or withdraw life support . Among those patients for whom life support was withheld, 58.8% were still alive 6 months post‐discharge.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Ferrand et al reported in 2001 that, in 113 French ICUs, 53% of ICU deaths were preceded by a decision to withhold or withdraw life support and that such decisions affected approximately 10% of all patients. These findings have been confirmed in more recent studies and it appears that the withholding of life support in critically‐ill patients does not necessarily lead to death in the ICU. Ferrand et al reported an ICU discharge rate of 43% after Wh, and a recent study reported an ICU discharge rate of 37% and a hospital discharge rate of 17%.…”
Section: Introductionsupporting
confidence: 59%
“…The analysis was adjusted for confounders age, gender, malignancy, smoking, chronic alcoholism, SOFA score at admission, night shift admissions, night shift deaths, weekend admission and weekend deaths (Table 4) [12]. Except Aspirin, all thromboprophylactic agents showed statistically signi cant reduction on ICU mortality (Table 4) (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…(a) SOFA scores at admission plotted against hospital mortality. The dotted lines represent high SOFA scores (12)(13)(14)(15)(16)(17), and the lines below (in order, 0 lowest, 11 highest) for lower SOFA scores at ICU admission. (b)Survival plot for SOFA scores at ICU admission.…”
Section: Figurementioning
confidence: 99%
“…In a recent worldwide audit of ICUs 13% of 9 524 included patients had a decision to withhold or withdraw life-sustaining treatment (1). Among 50% of death occurring in ICU, are secondary to a decision of withholding or withdrawal (WW) life support because of futility (2). Several ways to manage end of delivery sustaining therapies, have been described (3,4).…”
Section: Introductionmentioning
confidence: 99%